Chromosome genome assembly of the Camphora longepaniculata (Gamble) with PacBio and Hi-C sequencing data - Yan, Kuan; Zhu, Hui; Cao, Guiling; Meng, Lina; Li, Junqiang; Zhang, Jian; Liu, Sicen; Wang, Yujie; Feng, Ruizhang; Soaud, Salma A.; Elhamid, Mohamed A. Abd; Heakel, Rania M. Y.; et al. (Frontiers in Plant Science, 2024)
Camphora longepaniculata, a crucial commercial crop and a fundamental component of traditional Chinese medicine, is renowned for its abundant production of volatile terpenoids. However, the lack of available genomic information has hindered pertinent research efforts in the past. To bridge this gap, the present study aimed to use PacBio HiFi, short-read, and high-throughput chromosome conformation capture sequencing to construct a chromosome-level assembly of the C. longepaniculata genome. With twelve chromosomes accounting for 99.82% (766.69 Mb) of the final genome assembly, which covered 768.10 Mb, it was very complete. Remarkably, the assembly's contig and scaffold N50 values are exceptional as well-41.12 and 63.78 Mb, respectively-highlighting its excellent quality and intact structure. Furthermore, a total of 39,173 protein-coding genes were predicted, with 38,766 (98.96%) of them being functionally annotated. The completeness of the genome was confirmed by the Benchmarking Universal Single-Copy Ortholog evaluation, which revealed 99.01% of highly conserved plant genes. As the first comprehensive assembly of the C. longepaniculata genome, it provides a crucial starting point for deciphering the complex pathways involved in terpenoid production. Furthermore, this excellent genome serves as a vital resource for upcoming research on the breeding and genetics of C. longepaniculata.